Difusi Dakwah Digital di Era Covid-19 Bagi Generasi Millenial - Hoerotunnisa Nisa; Yazida Ichsan; Fifin Al Fionita; Faradina Nur Setianingsih (STAI Terpadu Yogyakarta, 2021)
The process of disseminating Islamic information from one person to another makes it easy for a good thing to run, which is what is called social diffusion as is the case with da'wah. Advances in digital technology and the use of social media have resulted in social linkages, including in religious life. References to religious knowledge place the internet as a reference, but its use in Indonesia itself is dominated by millennials who hold open and rational thoughts. Where the internet is used as an alternative source of knowledge, especially religious knowledge. The key to implementing digital technology in the religious field is one of them by means of preaching often called Digital Da'wah, which is a digital da'wah model of Islamic teaching that is easy, practical, efficient during the current pandemic. In this Covid-19 era, digital technology is very essential so that digital da'wah is used by scholars in the archipelago as a means of disseminating religious knowledge to the public, but still paying attention to health protocols to prevent the expansion of Covid-19. This digital da'wah is certainly virtual which has the advantage that it does not require tabliq akbar da'wah which requires consumption or da'wah costs. This virtual da'wah is only enough to use internet quotas and platforms as the best da'wah media during the Covid-19 pandemic is through several media such as Facebook, Instagram, and Twitter. Until the use of data and communication technology is an option that must be taken by the preacher. The pandemic should not dampen the spirit of da'wah, but on the contrary can make opportunities as an initial milestone in the rise of Islamic da'wah entering the industrial era 4.0. Flexibility in using da'wah media platforms is very helpful for the millennial generation in the midst of anxiety facing a pandemic.